2004
DOI: 10.1007/s00441-004-0970-y
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of the antennal glands in the crayfish Astacus leptodactylus (Crustacea, Decapoda): immunolocalization of Na+,K+-ATPase

Abstract: The involvement of the antennal urinary glands in the ontogeny of osmoregulatory functions was investigated during the development of Astacus leptodactylus by measurements of hemolymph and urine osmolality in juvenile and adult crayfish and by the immunodetection of the enzyme Na+,K+-ATPase. In stage II juveniles, 1-year-old juveniles, and adults, all of which were maintained in freshwater, urine was significantly hypotonic to hemolymph. In adults, chloride and sodium concentrations were much lower in urine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 45 publications
3
23
0
Order By: Relevance
“…diffusion access distances), or that the mechanism(s) of Na + uptake is (are) fundamentally different in neonates and adults. Notably, ontogenetic changes seen in hyper-regulating crustaceans are generally associated with anatomical and/or structural changes in the ion-transporting cells and organs (Charmantier and CharmantierDaures, 2001;Charmantier et al, 2002;Cieluch et al, 2004;Khodabandeh et al, 2005a;Khodabandeh et al, 2005b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…diffusion access distances), or that the mechanism(s) of Na + uptake is (are) fundamentally different in neonates and adults. Notably, ontogenetic changes seen in hyper-regulating crustaceans are generally associated with anatomical and/or structural changes in the ion-transporting cells and organs (Charmantier and CharmantierDaures, 2001;Charmantier et al, 2002;Cieluch et al, 2004;Khodabandeh et al, 2005a;Khodabandeh et al, 2005b).…”
Section: Discussionmentioning
confidence: 99%
“…In turn, physiological studies have clearly demonstrated that significant changes in the ability to cope with hypo-osmotic environments occur during the ontogenesis of the osmoregulatory organs in various crustacean groups, including cladocerans (daphnids), isopods, amphipods and decapods (crabs, lobsters, shrimps and crayfish) (Charmantier, 1998;Charmantier and Charmantier-Daures, 2001;Charmantier et al, 2002;Cieluch et al, 2004;Khodabandeh et al, 2005a;Khodabandeh et al, 2005b). The ontogenesis of the osmoregulation can occur at either the embryonic or the postembryonic phase (Charmantier and Charmantier-Daures, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The sections were pre‐incubated for 10 min in 0·01 mM Tween 20, 150 mM NaCI in 10 mM phosphate buffer, pH = 7·3, and then treated with 50 mM NH 4 Cl in phosphate‐buffered saline (PBS), pH = 7·3, for 5 min to mask the free aldehyde groups of the fixative. The sections were washed in PBS and incubated for 10 min with a blocking solution containing 1% bovine serum albumin (BSA) and 0·1% gelatin in PBS (Nebel et al , 2004, 2005; Khodabandeh et al , 2005 a , c ; Giffard‐Mena et al , 2006). Immunolocalization of the NKA was performed through immunofluorescence light microscopy using a mouse monoclonal antibody IgG α 5 (Hybridoma Bank, University of Iowa; http://dshb.biology.viowa.edu/) raised against the α ‐subunit of the chicken NKA (Takeyasu et al , 1988).…”
Section: Methodsmentioning
confidence: 99%
“…This is notable as brachyuran gills are typically either respiratory or osmoregulatory in nature, with AgNO 3 staining typically confined to just the osmoregulating gills. For example, only the posterior gills undergo staining in C. sapidus and many other brachyurans (Copeland and Fitzjarrell, 1968), and while some lamellae in all gills show staining in FW crayfish, it is localized to the central filaments of each gill (Dickson et al, 1991;Khodabandeh et al, 2005). AgNO 3 staining of larval H. rubra revealed that ion-transporting gills develop at late zoeal stages (i.e.…”
Section: Research Articlementioning
confidence: 99%